Hubungan Penggunaan KB Implant dengan Berat Badan dan Siklus Haid Akseptor KB - Hasliana Haslan; Indryani Indryani (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
An implant is a type of contraception in the form of an implant made of a type of silastic rubber containing hormones, mounted on the upper arm. Implants can cause menstrual disorders that are unable to menstruation and irregular bleeding occurs, bodyweight increases, causing acne, breast tension, intercourse feels dry. The purpose of this study was to determine the effect of the use of implanted contraception on body weight and menstrual cycles on acceptors in the working area of Ajangale Health Center. The type of research used in this study is the Analytic Survey with the design of Cross-Sectional Study. The population in this study were all implant acceptors in the working area of Ajangale Health Center in January to August 2019. The number of samples were29 peoples. The results showed that there was a relationship between the use of implant with acceptor body weight which the results of the chi square test obtained p-value = 0.015. There is a relationship between the use of implant with the acceptor’s menstrual cycle .with the results of the chi square test obtained p-value = 0.001. There is a relationship between implant use with acceptor's Weight and Menstrual Cycle.